Is Female Labour Force Participation Really Low and Declining in Pakistan? A look at Alternative Data Sources (The Pakistan Development Review, 1987)
For working out appropriate strategies and action programmes in order to fully utilize human resources for development and to advance the role and the status of women in society, it is essential that the statistical data collected on female participation in economic activity should reflect their position adequately and accurately in all the relevant sectors. In Pakistan, and other developing countries, the rural-agricultural segments, in the overall population have a large number of female workers who, directly and indirectly, contribute to agriculture, household and other unregistered rural activities. Similarly, in the urban organized sector, the work participation rate of women has registered a constant increase as a result of the social, economic and cultural changes which are taking place in these countries due to their development programmes.